Beyond surface tension-dominated water surface jumping - Xin Wang; Neng Xia; Chengfeng Pan; Jinsheng Zhao; Bo Hao; Lin Su; Dongdong Jin; Qingsong Xu; Xurui Liu; Xingyu Hou; Li Zhang (Nature Communications)
Abstract Water surface jumping motions of semi-aquatic insects are primarily rely on surface tension-dominated jumping mechanism to achieve impressive jumping performance. However, this mechanism faces an inherent physical constraint: the propulsion force must remain below the threshold required to break the water surface, limiting efficient momentum acquisition. Herein, we present a water surface jumping strategy that addresses the limitations of surface tension-dominated mechanism. Our approach allows the engineered jumper to achieve a record-breaking jumping height of 18 body lengths (63 cm) and take-off velocity of 100.6 body length/s (3.52 m/s). This strategy is built on three key design principles: (I) superhydrophobic body for floating on water surface, (II) light-weight, high-power actuation module capable of providing significant propulsion force within an ultrashort time, (III) well-engineered momentum transmission system for efficient kinetic energy transfer. The developed soft jumper based on these design principles advances the development of water environment related robotics.